Auditory rehabilitation of patients with neurofibromatosis Type 2 by using cochlear implants - Roehm, Pamela C. (2011)
OBJECT: The aim of this study was to determine whether patients with neurofibromatosis Type 2 (NF2) who have intact ipsilateral cochlear nerves can have open-set speech discrimination following cochlear implantation. METHODS: Records of 7 patients with documented NF2 were reviewed to determine speech discrimination outcomes following cochlear implantation. Outcomes were measured using consonant-nucleus-consonant words and phonemes; Hearing in Noise Test sentences in quiet; and City University of New York sentences in quiet and in noise. RESULTS: Preoperatively, none of the patients had open-set speech discrimination. Five of the 7 patients had previously undergone excision of ipsilateral vestibular schwannoma (VS). One of the patients who received a cochlear implant had received radiation therapy for ipsilateral VS, and another was undergoing observation for a small ipsilateral VS. Following cochlear implantation, 4 of 7 patients with NF2 had open-set speech discrimination following cochlear implantation during extended follow-up (15–120 months). Two of the 3 patients without open-set speech understanding had a prolonged period between ipsilateral VS resection and cochlear implantation (120 and 132 months), and had cochlear ossification at the time of implantation. The other patient without open-set speech understanding had good contralateral hearing at the time of cochlear implantation. Despite these findings, 6 of the 7 patients were daily users of their cochlear implants, and the seventh is an occasional user, indicating that all of the patients subjectively gained some benefit from their implants. CONCLUSIONS: Cochlear implantation can provide long-term auditory rehabilitation, with open-set speech discrimination for patients with NF2 who have intact ipsilateral cochlear nerves. Factors that can affect implant performance include the following: 1) a prolonged time between VS resection and implantation; and 2) cochlear ossification.